Combined treatment of xyloglucan derivative hydrogel and anti-C5a receptor antibody in preventing peritoneal adhesion. (1st October 2022) - Jiang, Lijie; Yao, Fanglian; Zhang, Ershuai; Yu, Qingyu; Yu, Chaojie; Chen, Ze; Chen, Jing; Yue, Zhiwei; Che, Pengcheng; Li, Junjie; Sun, Hong
ABSTRACT: Postoperative peritoneal adhesion is a common complication after surgery with high morbidity. In addition to improving surgical operations, medical therapy and physical barriers are the two main ways to prevent postoperative peritoneal adhesion. Satisfactory efficacy is not often obtained by the single antiadhesion method, and the combination of barrier therapy and antiadhesion drugs has attracted more attention. In this study, we first demonstrated that aberrant complement activation was associated with peritoneal injury and inflammatory responses. Correspondingly, blocking the C5a-C5aR axis reaction effectively reduced inflammatory reactions. Therefore, we creatively developed an integrated treatment of xyloglucan derivative (mXG) hydrogel and intravenous anti-C5a receptor antibody (anti-C5aRab) aimed at peritoneal adhesion, and then systematically evaluated the therapeutic efficacy using a sidewall defect-cecum abrasion model in mice. In vitro and in vivo experiments showed that the mXG hydrogel had good biocompatibility and degradability and could serve as a safe anti-adhesion barrier. The results showed that anti-C5aRab treatment could significantly inhibit peritoneal adhesions by reducing neutrophil infiltration and the expression of phosphorylated Smad2. Taken together, the mXG hydrogel integrated with anti-C5aRab showed superior antiadhesion performance and holds promising clinical applications in preventing peritoneal adhesion. Statement of significance: Postoperative peritoneal adhesion is an urgent problem to be solved after surgery. Previously, a biodegradable and thermoreversible xyloglucan derivative (mXG) hydrogel was developed that effectively prevented postoperative peritoneal adhesions, but obvious inflammatory responses and proliferation could still be observed. In addition, aberrant complement activation is associated with a variety of inflammatory diseases. We demonstrated that aberrant complement activation is involved in peritoneal adhesion. In this work, mXG hydrogel and intravenous anti-C5a receptor antibody (anti-C5aRab) were integrated to address peritoneal adhesions. The anti-C5aRab reduced the inflammatory responses. In addition, the mXG hydrogel was easy to use and effectively isolated the wound surface at the local injury site. Overall, this integrated treatment significantly improved the antiadhesion effect. Graphical Abstract: Image, graphical abstract